(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article analyzes the opportunities for tax evasion in the digital economy of the Republic of Uzbekistan, online trade, electronic services, electronic transactions and gives relevant proposals and recommendations.